2008
DOI: 10.1175/2007jamc1319.1
|View full text |Cite
|
Sign up to set email alerts
|

Along-Valley Structure of Daytime Thermally Driven Flows in the Wipp Valley

Abstract: High-resolution Doppler lidar observations obtained during the Mesoscale Alpine Program (MAP) 1999 field campaign are used to investigate the along-valley structure of daytime valley flows in the Wipp Valley, Austria. The observations show that under varying ambient conditions the valley flow increases in speed through a narrow section of the valley. Furthermore, the along-valley volume flux diverges along the valley segment under investigation, which suggests that the observed along-valley acceleration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…An acceleration of the along-valley flow has been observed in other valleys (e.g., Rucker et al 2008;Whiteman 2000). Such an acceleration is counterintuitive because one might expect a loss of valley airmass through the tributary valleys and side canyons (Zardi and Whiteman 2012).…”
Section: ) Spatial Wind Structure In the Salinas Valleymentioning
confidence: 97%
See 1 more Smart Citation
“…An acceleration of the along-valley flow has been observed in other valleys (e.g., Rucker et al 2008;Whiteman 2000). Such an acceleration is counterintuitive because one might expect a loss of valley airmass through the tributary valleys and side canyons (Zardi and Whiteman 2012).…”
Section: ) Spatial Wind Structure In the Salinas Valleymentioning
confidence: 97%
“…For example, in the case of an adjacent ocean, sea breezes can interact with valley flows to generate an extended sea breeze (e.g., Kondo 1990). In addition, synoptic flows can be subject to channeling into valleys (Whiteman 2000), and upvalley flows have been observed to accelerate along the valley floor (Rucker et al 2008). Across the valley, flow heterogeneities have been observed that result from dynamical effects caused by bends in the valley (De Wekker et al 2005;Weigel et al 2006) and thermally driven cross-valley circulations (Bader and Whiteman 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Groundbased remote sensing systems, such as Doppler lidars, have proved extremely useful for the description of the kinematic structure of cold fronts over complex terrain (Darby, et al, 1999;Neiman, et al, 2001;Darby and Poulos, 2006). During the MAP SOP such a Doppler lidar had been operated in the Wipp Valley to investigate south foehn (Flamant, et al, 2002;Durran, et al, 2003;Weissmann, et al, 2004;Zängl and Gohm, 2006;Marić and Durran, 2009) as well as thermally driven flows (Rucker, et al, 2008). In our cold front study we will use data from the same lidar.…”
Section: Introductionmentioning
confidence: 99%
“…These studies described a wind reversal twice per day at the slope and valley scale in response to local density gradients under fair-weather conditions. Eighty years later, these concepts remain central but it is known now that the local dynamics strongly depend on orographic arrangement and the literature shows that this cannot be generalized from one valley to another (Rucker et al, 2008;Duine et al, 2017;Giovannini et al, 2017). These local dynamics show a seasonal variability with solar forcing driving the relative period of daytime and night-time regimes (Bader and Whiteman, 1989;Whiteman, 2000;Zängl, 2004).…”
Section: Introductionmentioning
confidence: 99%